Validation of the AlamarBlue® Assay as a Fast Screening Method to Determine the Antimicrobial Activity of Botanical Extracts - Tyc, Olaf; Tomás-Menor, Laura; Garbeva, Paolina; Barrajón-Catalán, Enrique; Micol, Vicente (PLOS ONE, 2016)
Plant compounds are a potential source of new antimicrobial molecules against a variety of infections. Plant extracts suppose complex phytochemical libraries that may be used for the first stages of the screening process for antimicrobials. However, their large variability and complexity require fast and inexpensive methods that allow a rapid and adequate screening for antimicrobial activity against a variety of bacteria and fungi. In this study, a multi-well plate assay using the AlamarBlue® fluorescent dye was applied to screen for antimicrobial activity of several botanical extracts and the data were correlated with microbial colony forming units (CFU). This correlation was performed for three pathogenic model microorganisms: Escherichia coli (Gram negative bacteria), Staphylococcus aureus (Gram positive bacteria) and for the yeast-like fungi Candida albicans. A total of ten plant extracts from different Mediterranean plants, including several Cistus and Hibiscus species, were successfully tested. HPLC-DAD-ESI-MS/MS analysis was utilized for the characterization of the extracts in order to establish structure-activity correlations. The results show that extracts enriched in ellagitannins and flavonols are promising antibacterial agents against both Gram positive and Gram negative bacteria. In contrast, phenolic acids, anthocyanidins and flavonols may be related to the observed antifungal activity.